Development of Halloysite Nanohybrids-Based Films: Enhancing Mechanical and Hydrophilic Properties for Wound Healing - Francisco Ramón Rodríguez Pozo; Daiana Ianev; Tomás Martínez Rodríguez; José L. Arias; Fátima Linares; Carlos Miguel Gutiérrez Ariza; Caterina Valentino; Francisco Arrebola Vargas; Pablo Hernández Benavides; José Manuel Paredes; María del Mar Medina Pérez; Silvia Rossi; et al. (MDPI AG, 2024)
Most of the therapeutic systems developed for managing chronic skin wounds lack adequate mechanical and hydration properties, primarily because they rely on a single component. This study addresses this issue by combining organic and inorganic materials to obtain hybrid films with enhanced mechanical behavior, adhesion, and fluid absorption properties. To that aim, chitosan/hydrolyzed collagen blends were mixed with halloysite/antimicrobial nanohybrids at 10% and 20% (w/w) using glycerin or glycerin/polyethylene glycol-1500 as plasticizers. The films were characterized through the use of Fourier-transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), and electron microscopy. The mechanical properties were evaluated macroscopically using tensile tests, and at a nanoscale through atomic force microscopy (AFM) and nanoindentation. Thermodynamic studies were conducted to assess their hydrophilic or hydrophobic character. Additionally, in vitro cytocompatibility tests were performed on human keratinocytes. Results from FTIR, TGA, AFM and electron microscopy confirmed the hybrid nature of the films. Both tensile tests and nanomechanical measurements postulated that the nanohybrids improved the films' toughness and adhesion and optimized the nanoindentation properties. All nanohybrid-loaded films were hydrophilic and non-cytotoxic, showcasing their potential for skin wound applications given their enhanced performance at the macro- and nanoscale.